METHODOLOGY FOR OPTIMIZING THE PROFESSIONAL GROWTH OF PRIMARY EDUCATION STUDENTS BASED ON REFLECTIVE VIDEO TRAINING (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the development of pedagogical reflection in a higher educational institution and increasing the effectiveness of professional growth of students of primary education on the basis of reflexive video trainings. In order to develop pedagogical reflection and optimize the professional growth of students in a higher education institution, it is envisaged to use reflexive video trainings in class processes. Didactic support for the application of reflexive video trainings to the educational process, improvement of the educational methodology, and the possibility of increasing the effectiveness of the use of forms, methods, and tools have expanded.